2001
DOI: 10.1177/088307380101600913
|View full text |Cite
|
Sign up to set email alerts
|

Homocystinuria With Transverse Sinus Thrombosis

Abstract: A case of cerebral venous thrombosis caused by undiagnosed homocystinuria is reported. The pitfalls regarding the diagnosis of a potentially medically treatable condition are discussed. Cerebral venous thrombosis in children has a variable type of onset and a multiplicity of causes. This type of pathology, although not frequent, is more common than previously thought. Among the different etiologies, undiagnosed homocystinuria is not routinely considered. We report a case of venous thrombosis of the left transv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…Vitamin unresponsive forms of CBS deficiency seem to be more severe, manifesting earlier with more mental retardation or psychiatric disorders. CSVT due to CBS deficiency has been described (11)(12)(13), exceptionally as the only feature (14) as in our case. To our best of knowledge, CBSrelated post-partum CSVT has never been described before.…”
Section: Discussionsupporting
confidence: 63%
“…Vitamin unresponsive forms of CBS deficiency seem to be more severe, manifesting earlier with more mental retardation or psychiatric disorders. CSVT due to CBS deficiency has been described (11)(12)(13), exceptionally as the only feature (14) as in our case. To our best of knowledge, CBSrelated post-partum CSVT has never been described before.…”
Section: Discussionsupporting
confidence: 63%
“…Martinelli et al (50) reported that patients with hyperhomocysteinemia had a four-fold higher risk to developing CVST. It is important to note that among the different etiologies, undiagnosed homocystinuria is not routinely considered (51, 52).…”
Section: Risk Factorsmentioning
confidence: 99%
“…Bacterial or viral infections, [3][4][5][6] head or vascular trauma, surgery, immobilization or obesity, 17,22,24,32 jugular 33 or subclavian central venous lines, 7,34,35 solid tumors, leukemia and lymphomas, 8 autoimmune diseases, 9 renal diseases, 10 metabolic disorders, [13][14][15] birth asphyxia, 12 and cardiac malformations were predefined as predisposing clinical conditions. 2 In addition, drugs such as steroids 2,20,22,32 and Escherichia coli asparaginase, the use of sympathomimetics, coagulation factor concentrates, or oral contraceptives, and nicotine abuse were classified as underlying conditions.…”
Section: Underlying Clinical Conditionsmentioning
confidence: 99%
“…1 The disease is serious, and predisposing and influencing factors should be unraveled to identify patients at risk and to establish treatment regimens in children. Local or systemic infections, [3][4][5][6] vascular trauma, 7 cancer, acute lymphoblastic leukemia, drug toxicity, 8 lupus erythematosus, 9 nephrotic syndrome, 10 dehydration, 11 asphyxia, maternal problems during pregnancy, 12 Behçet's disease, 2 and metabolic disorders [13][14][15] have been described as predisposing factors.…”
mentioning
confidence: 99%